STUDENTS’ MOTIVATION IN LEARNING ENGLISH SPEAKING AT THE EIGHTH GRADE OF SMP NEGERI 3 DHARMA CARAKA - Ndruru, Intan Sari (Universitas Nias Raya, 2024)
This research aimed at analyzing students’ motivation at the eighth grade of SMP Negeri 3 Dharma Caraka. This research was designed by using descriptive qualitative method. In analyzing the data, the researcher used theory of Gay (2012), they were reading and memoing, describing, and classifying. In this research, the source of the data was taken from 24 students at the Eighth Grade of SMP Negeri 3 Dharma Caraka. Technique of the data collection were observation and interview. The result of the research showed that they were experienced by eighth grade students of SMP Negeri 3 Dharma Caraka by intrinsic and extrinsic motivation. The intrinsic motivations were self desire, satisfaction, challenge/competition, and good habits. The extrinsic motivations were praise, advice, teacher, parents and environment, and reward. The students who had intrinsic motivations were active in speaking activity because they derived from themselves. It reflects the internal drive to achieve personal goals, serving as primary motivator for success. Meanwhile, the students who had extrinsic motivation were active in speaking because they have expectation to get high score, and other reward from the teacher, and praise from the teacher and friends. But, most of students are motivated in extrinsic motivations, they were active in speaking activity because from the environment and other reward. It is suggested to English teacher to create a good atmosphere while teaching in the classroom especially in speaking English. Moreover, teacher need to motivate their students by designing activities that are interesting and relevant to daily life that encourage interaction and conversation.